Electrical characteristics of gated‐anode diodes based on normally‐off GaN HEMT structures for rectenna applications. Issue 21 (6th July 2021) - Takahashi, Hidemasa; Ando, Yuji; Tsuchiya, Yoichi; Wakejima, Akio; Hayashi, Hiroaki; Yagyu, Eiji; Kikkawa, Koichi; Sakai, Naoki; Itoh, Kenji; Suda, Jun
Abstract: Here, a gated‐anode diode (GAD) is proposed where an anode electrode is formed by connecting a gate electrode and an ohmic electrode of a normally‐off GaN HEMT for a 5.8 GHz rectenna. A wide recessed gate GaN GADs were prepared and the recess length dependence of their electrical characteristics was investigated. Typical DC characteristics of the HEMTs are a threshold voltage ( V th ) of +0.3 V and a maximum drain current ( I max ) of 300 mA/mm. The GADs showed the characteristics of maximum forward current ( I f ) of 350 mA/mm, reverse breakdown voltage ( BV r ) of 40 V, and off‐state capacitance ( C off ) of 0.28 pF/mm by using optimized recess length. We constructed SPICE model of the GADs. The SPICE simulation predicted a rectifier efficiency of 81% and a DC output power of 10 W for bridge type 5.8 GHz rectifier using four GADs with each gate width of 0.8 mm.